The feasibility of text reminders to improve medication adherence in adolescents with asthma. (11th December 2015) - Johnson, Kevin B; Patterson, Barron L; Ho, Yun-Xian; Chen, Qingxia; Nian, Hui; Davison, Coda L; Slagle, Jason; Mulvaney, Shelagh A
Abstract : Objective Personal health applications have the potential to help patients with chronic disease by improving medication adherence, self-efficacy, and quality of life. The goal of this study was to assess the impact of MyMediHealth (MMH) – a website and a short messaging service (SMS)-based reminder system – on medication adherence and perceived self-efficacy in adolescents with asthma. Methods We conducted a block-randomized controlled study in academic pediatric outpatient settings. There were 98 adolescents enrolled. Subjects who were randomized to use MMH were asked to create a medication schedule and receive SMS reminders at designated medication administration times for 3 weeks. Control subjects received action lists as a part of their usual care. Primary outcome measures included MMH usage patterns and self-reports of system usability, medication adherence, asthma control, self-efficacy, and quality of life. Results Eighty-nine subjects completed the study, of whom 46 were randomized to the intervention arm. Compared to controls, we found improvements in self-reported medication adherence ( P = .011), quality of life ( P = .037), and self-efficacy ( P = .016). Subjects reported high satisfaction with MMH; however, the level of system usage varied widely, with lower use among African American patients. Conclusions MMH was associated with improved medication adherence, perceived quality of life, and self-efficacy. Trial Registration This project was registered under http://clinicaltrials.gov/ identifier NCT01730235.